Optometry Outreach in Indigenous Communities in British Columbia, Saskatchewan, and Manitoba - Warren, Adrianna (University of Waterloo, 2023)
Introduction: Inuit, Métis, and First Nations, the three main Indigenous groups within Canada, face disproportionate barriers to access for primary eye and vision care. Optometrists visit rural and remote Indigenous communities to provide outreach care to areas without a local optometrist; however, the approach is fragmented and not well represented. The purpose of this project is to assess the current state of outreach optometry within Indigenous communities by surveying optometrists who provide outreach care. Methods: In collaboration with the provincial optometry regulatory bodies, eligible participants were identified as optometrists who travel outside of their primary clinics to provide care within non-urban Indigenous communities. A questionnaire was developed through iterative stakeholder review for phase I of the study. The online questionnaire captured the delivery of care across one year (2022). The process of planning logistics, distances travelled, patient care provided and associated expenses were queried. A Semi-structured interview guide was developed for phase II of the study. One-on-one interviews expanded on questionnaire themes, providing insight into individual experiences. Data was collated through descriptive statistics and thematic coding for case and cross-case analysis. Results: The overall response rate was 50% (18/36) for the questionnaire and 30.5% (11/36) for the interview. Total questionnaire responses represent 96 outreach visits, 312.5 optometry clinic days, and 8,386 patient encounters across 64 communities in the three provinces. Optometrists coordinate with health center employees and school contacts to plan outreach visits, travelling primarily north to some of the most remote areas within each province. Overall Euclidean distances between participants primary clinic locations and communities visited ranged from 65 to 1405 kilometers (kms) (median: 438 kms). Costs per clinic day were highly variable ($174.44 - $3,800, mean: $765 per clinic day). Challenges reported were ...